Regional Potential Optimization Model in Increasing Local Revenue of Maybrat Regency, West Papua Province - Bernard Sagrim; Khasan Effendy; Ngadisah; Sampara Lukman (GoAcademica Research & Publishing, 2020)
This study aims to find an optimal model for the development of regional potential owned by Maybrat Regency, West Papua Province, to increase local revenue for its people's welfare. Qualitative methods are used in this research using a post-positivism paradigm design, which seeks to reveal a social reality that ontologically can never be fully understood due to the limitations of human nature. The results show that the regional potential optimization model in Maybrat Regency is different from other regions because Maybrat Regency has special autonomy, which provides the broadest possible opportunity for local governments to manage all the potential to increase local revenue. The increase in the original region requires the support of political stability, availability, and quality of human resources, the quality of supporting facilities to create a good investment climate. West Papua Maybrat Regency Government.